2006
DOI: 10.1111/j.1601-183x.2006.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcoholism is associated with GALR3 but not two other galanin receptor genes

Abstract: The neuropeptide galanin is widely expressed in the periphery and the central nervous system and mediates diverse physiological processes and behaviors including alcohol abuse, depression and anxiety. Four genes encoding galanin and its receptors have been identified (GAL, GALR1, GALR2 and GALR3). Recently we found that GAL haplotypes were associated with alcoholism, raising the possibility that genetic variation in GALR1, GALR2 and GALR3 might also alter alcoholism risk. Tag single nucleotide polymorphisms (S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(48 citation statements)
references
References 60 publications
(71 reference statements)
3
44
0
Order By: Relevance
“…Furthermore, the GAL 3 gene, but not the GAL 1 and GAL 2 genes, was associated with alcoholism in Finnish Caucasians (Belfer et al, 2007), whereas in the same study, no association of the GAL 3 locus with alcoholism was observed in American Plains Indians. This difference 152 might be due to the fact that the frequency of SNP rs3091367 differed significantly between the two populations (Belfer et al, 2007). Furthermore, the GAL 3 /GAL risk diplotypes display a significant association with alcoholism, more than GAL or GAL 3 alone (Belfer et al, 2007).…”
Section: B Addiction-related Behaviormentioning
confidence: 62%
See 1 more Smart Citation
“…Furthermore, the GAL 3 gene, but not the GAL 1 and GAL 2 genes, was associated with alcoholism in Finnish Caucasians (Belfer et al, 2007), whereas in the same study, no association of the GAL 3 locus with alcoholism was observed in American Plains Indians. This difference 152 might be due to the fact that the frequency of SNP rs3091367 differed significantly between the two populations (Belfer et al, 2007). Furthermore, the GAL 3 /GAL risk diplotypes display a significant association with alcoholism, more than GAL or GAL 3 alone (Belfer et al, 2007).…”
Section: B Addiction-related Behaviormentioning
confidence: 62%
“…This difference 152 might be due to the fact that the frequency of SNP rs3091367 differed significantly between the two populations (Belfer et al, 2007). Furthermore, the GAL 3 /GAL risk diplotypes display a significant association with alcoholism, more than GAL or GAL 3 alone (Belfer et al, 2007). A significant association of a SNP in intron 2 of the GAL gene and heroin addiction was observed in US Caucasians (Levran et al, 2008), and more recently the involvement of galanin in opioid addiction was further suggested by a candidate gene association study conducted including .100 well phenotyped long-term opioid addicts undergoing opioid maintenance therapy and well matched healthy controls.…”
Section: B Addiction-related Behaviormentioning
confidence: 99%
“…Thus, galanin interacts with 5-HT1A receptors, and galanin antagonists and agonists have anxiolytic and antidepressive effects in animal experiments (144)(145)(146)(147)(148)(149)(150)(151). Interestingly, association of genes encoding galanin and/or GalR3 has been reported for psychiatric phenotypes (152)(153)(154), including panic disorder (155), depression-related parameters (156)(157)(158), and nicotine dependence (159,160).…”
Section: Significancementioning
confidence: 99%
“…For GAL, so far three G-protein-coupled receptors (galanin receptor 1 (GALR1), GALR2, GALR3) have been described and are expressed in both the central and peripheral nervous system (reviewed in Mitsukawa et al, 2008). Genetic associations of PPGAL and the genes encoding GALR3 have been reported for psychiatric phenotypes (Belfer et al, 2006(Belfer et al, , 2007Levran et al, 2008;Unschuld et al, 2008). In animal studies, GAL has been shown to modulate anxious and depressive behavior (reviewed in Kuteeva et al, 2008).…”
Section: Introductionmentioning
confidence: 99%